2019
DOI: 10.3389/fpsyt.2019.00025
|View full text |Cite
|
Sign up to set email alerts
|

D-Serine: Potential Therapeutic Agent and/or Biomarker in Schizophrenia and Depression?

Abstract: D-Serine is a potent co-agonist at the NMDA glutamate receptor and has been the object of many preclinical studies to ascertain the nature of its metabolism, its regional and cellular distribution in the brain, its physiological functions and its possible clinical relevance. The enzymes involved in its formation and catabolism are serine racemase (SR) and D-amino acid oxidase (DAAO), respectively, and manipulations of the activity of those enzymes have been useful in developing animal models of schizophrenia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 121 publications
3
74
0
2
Order By: Relevance
“…Initially, it was discovered in the brain but has more recently been studied in the neural retina [13]. D-serine, formed by the racemization of L-serine by serine racemase (SRR) [13], functions as a neurotrophic factor and as a co-agonist for N-methyl-D-aspartate receptors (NMDARs) [37]. In the brain, NMDARs normally bind glutamate and glycine, but data suggests preferential or higher affinity binding to D-serine in the retina [13,38].…”
Section: The Role Of D-serinementioning
confidence: 99%
See 2 more Smart Citations
“…Initially, it was discovered in the brain but has more recently been studied in the neural retina [13]. D-serine, formed by the racemization of L-serine by serine racemase (SRR) [13], functions as a neurotrophic factor and as a co-agonist for N-methyl-D-aspartate receptors (NMDARs) [37]. In the brain, NMDARs normally bind glutamate and glycine, but data suggests preferential or higher affinity binding to D-serine in the retina [13,38].…”
Section: The Role Of D-serinementioning
confidence: 99%
“…Irrespective of NMDAR functions, the importance of D-serine is evidenced by pathologies that are directly linked to D-serine irregularities. D-serine insufficiency has been associated with psychiatric and neurodevelopmental disorders [37]. Supplementation with D-serine has proven to mitigate some of the symptoms of psychosis [37].…”
Section: The Role Of D-serinementioning
confidence: 99%
See 1 more Smart Citation
“…Using kidney tubular cell lines (HK-2) and primary cultures of kidney tubular cells, one study suggested the toxic mechanism of higher doses of d-serine as the induction of cell cycle arrest, pro-inflammatory response, and apoptosis via effector molecules of ER stress [40]. Higher doses of d-serine have been used in some clinical studies in schizophrenia and cerebellar ataxia [41,42], as a potential activator of NMDAR. In these studies, potential side-effects such as proteinuria and abnormal kidney values were sporadically reported, although the causal relationship remains unclear [43,44].…”
Section: Physiological Function Of D-serine In Kidneymentioning
confidence: 99%
“…Îñíîâûâàÿñü íà ïîëîaeèòåëüíûõ êëèíè÷åñêèõ ðåçóëüòàòàõ ñ ãëèöèíîì, áûëà ïðîâåäåíà ñåðèÿ èññëåäîâàíèé ñ àëüòåðíàòèâíûì àãîíèñòîì ãëèöèí-ñàéòà, D-ñåðèíîì [62]. Ïåðâîíà÷àëüíîå êëè-íè÷åñêîå èññëåäîâàíèå âêëþ÷àëî 29 ïàöèåíòîâ, ëå÷èâøèõñÿ â òå÷åíèå 6 íåä ëèáî D-ñåðèíîì, ëèáî ïëàöåáî.…”
Section: перспективы применения аминокислот ацилкарнитинов и препараunclassified